IMPLEMENTASI PERATURAN BUPATI BARITO TIMUR NOMOR 6 TAHUN 2015 TENTANG PENGADAAN BARANG/ JASA DI DESA - John Karigas; Irawanto Irawanto; M. Jamili M. Jamili (REFORMASI, 2017)
Abstract: Implementation of Barito Timur Regency’s RegulationNumber 6 year 2015 on Procurementof Goods/ Services in the Village. The purpose of this research is to know the implementation of Regulation of Barito Timur Regent Number 6 Year 2015 concerning Procurement of Goods/ Services in Village from Communication factor, Human Resources and Bureaucracy Structure (George Edward III dalam Budi Winarno, 2012:126-151). But it will also give recommendation for Local Government in implementing Procurement of Goods/ Services in Village East Barito Regency. The research method used is descriptive method with qualitative approach. Data collection was done by interview and documentation techniques. Triangulation technique is used to check the validity of research data. Data analysis in this research using steps Miles and Huberman (1992), is the process of analysis by using several components consisting of data reduction, presentation or display data and the conclusion/ verification. The results showed that the Implementation of Barito Timur Regency’s Regulation Number 6 year 2015 on Procurementof Goods/ Services in the Village District Dusun East has not run optimally. Implementation still faces fundamental obstacles in communication is lack of socialization intensity done to executor of policy of procurement of goods / services in village. Another obstacle is the human resources, namely the low ability of procurement of goods / services in the village. While in the bureaucratic structure there has been no dispersion of responsibilities among the implementing Team for procurement of goods / services in the village. Keywords: Implementation, Procurement Policy of Goods/ Services in The Village.